Causal effects of physical activity on the risk of overall ovarian cancer: A Mendelian randomization study - Jing Wang; Huanling Zhao; Jiahao Zhu; Minmin Jiang (Digital Health, 2023)
Objective Inconsistent results were reported on the association of physical activity with ovarian cancer. However, given the limitations of confounders and inverse causation, the validity of the association remained unclear. Therefore, we conducted a two-sample Mendelian randomization analysis, which can effectively avoid the aforementioned interference, to evaluate whether physical activity had a protective effect on ovarian cancer. Methods The exposure of interest was physical activity (both self-reported moderate-to-vigorous physical activity and accelerometer-measured physical activity). Summary statistics for physical activity traits were recruited from the UK Biobank ( n   =  91,084–377,234), whereas ovarian cancer summary genetic data were obtained from a genome-wide association study involving 25,509 cases and 40,941 healthy individuals. The inverse variance weighted approach was used as the primary Mendelian randomization method. Sensitivity analyses using Mendelian randomization-Egger regression, weighted median, and Mendelian randomization pleiotropy residual sum and outlier were also performed. Results The Mendelian randomization analyses indicated that there was no effect of moderate-to-vigorous physical activity (odds ratio, 1.11; 95% confidence interval: 0.66–1.85; P    =   0.702), accelerometer-measured “average acceleration” (0.99 [0.91–1.08]; P    =   0.848), and “overall activity” physical activity (0.97 [ 0.48–1.95]; P    =   0.927) on the risk of overall ovarian cancer. However, “overall accelerations” physical activity (0.18 [0.05–0.64]; P    =   0.008) were suggestively related to a lower risk of endometrioid ovarian cancer. Conclusions The Mendelian randomization analyses suggested that physical activity may not help to decrease the risk of overall ovarian cancer.